Worker cooperatives and democratic governance - John H. Pencavel (Institute for the Study of Labor (IZA), 2012)
A worker co-operative is a firm that is owned and managed by those who work in it. This paper provides a selective review of research in economics on worker cooperatives. It concentrates on the volatility of earnings and employment in the co-ops compared with conventional capitalist firms; on the long-term viability of co-ops; on the relative productive efficiency of co-ops; and on problems of democratic governance within co-ops. Using modern empirical methods applied to large numbers of observations, recent research has substantially enhanced our understanding of worker co-ops.
Keywords: J54; 330; worker cooperatives; comparative efficiency; viability; Genossenschaft; Selbstverwalteter Betrieb; Produktivität; Wirtschaftliche Effizienz; Unternehmenserfolg; Wirtschaftsdemokratie; Theorie